Assessing the language availability, readability, suitability and comprehensibility of heat-health messaging content on health authority webpages and online resources in Canada - Emily J. Tetzlaff; Kristina-Marie T. Janetos; Katie E. Wagar; Farah Mourad; Melissa Gorman; Victor Gallant; Glen P. Kenny (PEC Innovation)
Objectives: Heat-health communication initiatives are a key public health protection strategy. Therefore, understanding the potential challenges that all Canadians and specific groups, such as those facing literacy barriers and non-native language speakers, may experience in accessing or interpreting information, is critical. Methods: This study reviewed and evaluated the language availability, readability, suitability, and comprehensibility of heat-related webpages and online resources (n = 417) published on public health authority websites in Canada (n = 73). Six validated readability scales and a comprehensibility instrument were used. Results: Most content was presented in English (90 %); however, only 7 % of the online resources were available in more than one language. The average reading grade level of the content (grade 8) exceeded the recommended level (grade 6), and only 22 % of the content was deemed superior for suitability and comprehensibility. Conclusions: Our study evaluating web-based materials about extreme heat published by Canadian health authorities provides evidence that the current language availability, readability, suitability, and comprehensibility may be limiting the capacity for members of the public to discern key messaging. Innovation: To ensure all Canadians can access and interpret information related to heat-health protection, public health authorities may consider translating their materials into additional languages and incorporating a readability evaluation to improve public understanding.